(3JcfhdhLjG COH GdCWaGd (B/s - (3THdhd,CMeO aVd s ((3GdEScfOQjI (B:s (3OGQ GdhaGA dOfjG GdWHGYI h GdfTQ ,s, 1999)
(3JMGhd aUhd gPG GdcJGH Cf JQJjH GdChQGb GdeJUdI HbVjI COH GdWad h KbGaJg hYGdeg Ydi eGFOI GdegJejf HgG aj hWffG GdYQHj h Cf JaJM fbGTG eajOG h eKeQG eY GdCOHGA h GdeKbajf h GdeYdejf h GdJQHhjjf aVdG Yf GdBHGA h GdCegGJ Mhd COH GdWad h KbGaJg GdGdcJQhfjI h eOi GdGSJaGOI ef GdJbfjGJ GdMOjKI aj JKbja GdWad GdYQHj h JYdjeg h JQajgg(B, (3h JCOjHg (B.(3CjVG jMGhd gPG GdcJGH Gdhbha Ydi YfGUQ COHjI h KbGajI LOjOI HOCJ JSQi aj cjGf GdeLJeY Ohf Cf jYi cKQhf eef dge YdGbI eHGTQI HKbGaI GdWad GdYQHj h COHg HCgejI eG jMOK Ch NWhQJg aj Jchjf Wad YQHj eZGjQ dCWaGd GdYbhO GdSGHbI hgh GdbQf GdMGOj h GdYTQjf hPdc ef NdGd GdaUhd GdJGdjI (B,(3eaGgje CSGSjI GdKbGaI GdGdcJQhfjI CTcGd h eVGejf LOjOI bUU GdcJQhfjI ddCWaGd (B,(3UMGaI GdCWaGd GdGdcJQhfjI (B, (3GdMGShH h GdGfJQfJ ddJYdje GdHQfGeL ENQGLg h NUGFUg ehGbY h ebGg ddCWaGd (B, (3GdeSGHbGJ GdGdcJQhfjI (B, (3CNjQG cja fMei CWaGdfG ef eNGWQ GdMGShH ? s
Keywords: (3COH GdCWaGds; (3GdCOHs; (3GdJcfhdhLjGs